La visibilità come enigma : Merleau-Ponty a partire da Cézanne - Negri, Federica (Scenari, 2021)
The philosophical path of Merleau-Ponty, from phenomenology to the ontological project of the last writings, could be read as a long reflection on the enigma of visibility. In this sense, the figure of Cézanne is significant for his attempt to unveil the “roots of being”, the mystery of the appearance of visibility. Thus painting becomes one of the most authentic ways of searching for the new ontological enterprise of the French philosopher, in which we are witnessing the unfolding of Being.